A kind of low-resistance and low-radiation steelable triple-silver coated glass and preparation method thereof
Patent Information
- Application Number
- CN202410885423.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-02-14
AI Technical Summary
The existing three-silver coated glass has problems such as high process difficulty in the multi-layer film structure, low purity of single-layer film components, poor stability, and difficult processing, which affects the performance stability and yield of the product.
It adopts the design of low-resistance and low-emissivity steel triple silver-coated glass. By sequentially setting 18 layers of films on the glass substrate, including silicon nitride oxide, niobium oxide, zinc oxide, silver yttrium, ITO, AZO, TZO and other materials, magnetic It is prepared by controlled sputtering method, controls the process atmosphere and target gas purity, reduces the influence of gas cross-flow, and uses an yttrium metal layer to improve the density and hardness of the film layer.
Coated glass that achieves low resistance, high transmittance and good processing performance improves process stability and yield, extends product service life, and reduces production costs.
Smart Images

Figure CN118652056A8_ABST
Abstract
Description
Background Art
[0001] The invention relates to the field of low-radiation magnetron sputtering coated glass, and in particular provides a low-resistance steel-silver triple-silver low-radiation coated glass and a preparation method thereof. Technical Field
[0002] The present invention relates to the field of low-radiation magnetron sputtering coated glass, and specifically provides a low-resistance steel-silver low-radiation glass that can reach 0.01 and has extremely high reflectivity to mid- and far-infrared rays, thus having excellent energy-saving effects and being widely used in the fields of high-end buildings and new energy automobile glass, and is suitable for use in both the hot summer season in the south and the cold winter climate in the north.
[0003] Triple silver coated glass is generally made by depositing 15-20 layers of single-layer films (combination of metal layer and dielectric layer) on the glass surface. The combination of single-layer films of different materials changes its basic optical and electrical properties, achieving the purpose of energy saving and decoration. The more film layers there are, the more complex the film system is, and the higher the technical difficulty is. For example, the influence of cross-gas caused by the different process atmospheres of different single-layer films (affecting the purity of the single-layer film components), the stability of each single-target sputtering process, the influence of the increase in the number of film layers on the overall light transmittance of the product, and the difficulty of processing triple silver products in the deep processing process. In order to solve the problems existing in the existing triple silver coated glass products, how to maintain excellent and stable performance and improve the yield rate of subsequent processing is a topic worth exploring. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the above-mentioned prior art and provide a low-resistance, low-radiation, steelable triple-silver coated glass and a preparation method thereof.
[0005] The technical solution of the present invention is: A low-resistance, low-radiation, steelable triple-silver coated glass comprises a glass substrate, characterized in that the triple-silver coated layer is a laminated structure arranged in sequence: a primer layer, a first transition layer, a first seed layer, a first functional layer, a first barrier layer, a second transition layer, a second dielectric layer, a second seed layer, a second functional layer, a second barrier layer, a third transition layer, a third dielectric layer, a third seed layer, a third functional layer, a third barrier layer, a fourth transition layer, a fourth dielectric layer and a protective layer arranged on the glass substrate.
[0006] On the basis of the above technical solutions, there are the following further technical solutions: The bottom layer is a silicon oxynitride layer with a thickness of 15-20 nm.
[0007] The first transition layer is a niobium oxide layer with a thickness of 8-10nm, the first seed layer is a zinc oxide layer with a thickness of 10-13nm, the first functional layer is a silver yttrium layer with a yttrium content of 2.5% and a thickness of 12-18nm, and the first barrier layer is an ITO layer with a thickness of 5-10nm; The second transition layer is an AZO layer with a thickness of 8-12nm, the second dielectric layer is a TZO layer with a thickness of 40-50nm, the second seed layer is a zinc oxide layer with a thickness of 10-15nm, the second functional layer is a silver yttrium layer with a yttrium content of 2.5% and a thickness of 6-10nm, and the second barrier layer is an ITO layer with a thickness of 5-10nm; The third transition layer is an AZO layer with a thickness of 8-12nm, the third dielectric layer is a TZO layer with a thickness of 50-60nm, the third seed layer is a zinc oxide layer with a thickness of 10-15, the third functional layer is a silver yttrium layer with a yttrium content of 2.5% and a thickness of 10-15nm, and the third barrier layer is a titanium layer with a thickness of 0.8-1.2nm; The fourth transition layer is an AZO layer with a thickness of 8-12 nm, the fourth dielectric layer is a TZO layer with a thickness of 25-35 nm, and the protective layer is a zirconium oxide layer with a thickness of 3-5 nm.
[0008] The present invention also provides a method for preparing low-resistance, low-radiation, steelable triple-silver coated glass, which is characterized by comprising the following steps: (1) A base silicon oxynitride layer with a thickness of 15-20 nm was prepared on a glass substrate by reaction after sputtering of a silicon-aluminum rotating target. The process gases used were argon, oxygen and nitrogen. The deposition pressure was 0.0035 mbar, and Ar:O2:N2=3.2:1:2.3; (2) A first transition layer of niobium oxide is prepared on the base layer with a thickness of 5-10 nm, which is obtained by sputtering a niobium oxide rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.005 mbar, and Ar:O2=50:1; (3) A first seed layer of zinc oxide is prepared on the first transition layer with a thickness of 10-15 nm, which is obtained by reaction after sputtering of a zinc-aluminum rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.006 mbar, and Ar:O2=1:1.6; (4) Preparing a first functional layer of silver-yttrium layer on the first seed layer, wherein the yttrium content is 2.5% and the thickness is 12-18 nm, obtained by sputtering a silver-yttrium alloy flat target, the process gas used is pure argon, and the deposition pressure is 0.003 mbar; (5) Preparing a first barrier layer ITO layer on the first functional layer with a thickness of 5-10 nm, obtained by direct sputtering of an indium tin oxide rotating target, using pure argon as the process gas and a deposition pressure of 0.003 mbar; (6) A second transition layer AZO layer is prepared on the first barrier layer with a thickness of 8-12 nm, which is obtained by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.004 mbar, and Ar:O2=50:1; (7) A second dielectric layer TZO layer with a thickness of 40-50 nm is prepared on the second transition layer by sputtering of zinc oxide tin rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.004 mbar, and Ar:O2=50:1; (8) A second seed layer of zinc oxide is prepared on the second dielectric layer with a thickness of 10-15 nm, which is obtained by reaction after sputtering of a zinc-aluminum rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.006 mbar, and Ar:O2=1:1.6; (9) Preparing a second functional layer of silver-yttrium layer on the second seed layer, wherein the yttrium content is 2.5%, the thickness is 6-10 nm, and it is obtained by sputtering a silver-yttrium alloy flat target. The process gas used is pure argon gas, and the deposition pressure is 0.003 mbar; (10) Preparing a second barrier layer ITO layer on the second functional layer with a thickness of 5-10 nm, obtained by direct sputtering of an indium tin oxide rotating target, using pure argon as the process gas and a deposition pressure of 0.003 mbar; (11) A third transition layer AZO layer with a thickness of 8-12 nm is prepared on the second barrier layer by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.004 mbar, and Ar:O2=50:1; (12) A third dielectric layer TZO layer is prepared on the third transition layer with a thickness of 50-60 nm, which is obtained by zinc oxide tin target sputtering. The process gases used are argon and oxygen, the deposition pressure is 0.004 mbar, and Ar:O2=50:1; (13) Preparing a third seed layer of zinc oxide on the third dielectric layer with a thickness of 10-15 nm, obtained by reaction after sputtering of a zinc-aluminum rotating target, using argon and oxygen as process gases, with a deposition pressure of 0.006 mbar, and Ar:O2=1:1.6; (14) Preparing a third functional layer of silver-yttrium layer on the third seed layer, wherein the yttrium content is 2.5% and the thickness is 10-15 nm, obtained by sputtering a silver-yttrium alloy flat target, the process gas used is pure argon, and the deposition pressure is 0.003 mbar; (15) Preparing a third barrier titanium layer on the third functional layer with a thickness of 0.8-1.2 nm, obtained by sputtering a pure titanium flat target, using pure argon as the process gas and a deposition pressure of 0.003 mbar; (16) A fourth transition layer AZO layer is prepared on the third barrier layer with a thickness of 8-12 nm, which is obtained by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, the deposition pressure is 0.004 mbar, and Ar:O2=50:1; (17) A fourth dielectric layer TZO layer is prepared on the fourth transition layer with a thickness of 25-35 nm, which is obtained by zinc oxide tin target sputtering. The process gases used are argon and oxygen, the deposition pressure is 0.004 mbar, and Ar:O2=50:1; (18) A protective zirconium oxide layer with a thickness of 3-5 nm is prepared on the fourth dielectric layer. It is obtained by sputtering a zirconium oxide rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.003 mbar, and Ar:O2=100:1.
[0009] Due to the adoption of the above technical solution, the present invention has the following advantages: The low-resistance, transparent, triple-silver, low-emissivity coated glass has 14 layers of 18 single-layer films on the glass substrate in an almost pure argon process atmosphere, which greatly reduces the problem of low purity of the single-layer film due to cross-talk between different reaction gases from a process perspective (because even if the production line has a good gas isolation design, it is impossible to completely prevent cross-talk between gases, it can only reduce cross-talk), and the selected material not only has a stable process and an extremely high sputtering rate, but also avoids the problem of many production lines affecting production efficiency due to insufficient number of targets.
[0010] The low-resistance steel triple silver low-emissivity coated glass uses a silver-yttrium metal layer as the functional layer material. Compared with the traditional pure silver metal layer, the target material grain size is finer and more uniform, the deposited film layer is denser, and has better electrical properties. At the same time, in terms of mechanical properties, compared with the active pure silver metal layer, it has higher hardness and better corrosion resistance, so that the final low-emissivity coated product has better processing performance, better environmental tolerance, and longer service life.
[0011] The low-resistance steelable triple-silver low-emissivity coated glass has ITO layers as the first and second barrier layers. The film has low absorption and is transparent, and has almost no effect on the product transmittance (greatly ensuring the overall transmittance of the product). At the same time, the film has good electrical properties and energy-saving effects after tempering. The functional layer material makes the product resistance lower and the overall energy-saving effect better. The third barrier layer material is titanium. Compared with the traditional nickel-chromium metal layer, the film has a lower extinction coefficient. While protecting the functional layer, it minimizes the impact on the product transmittance. At the same time, metal is selected as the outermost barrier layer material, and the protective layer zirconium oxide film (high hardness and low friction coefficient) is matched, so that the coated glass has more excellent processing resistance, can adapt to more harsh processing environments, and is more easily accepted by the market.
[0012] The low-resistance steelable triple-silver low-emissivity coated glass has a first transition layer of niobium oxide, which has a relatively high refractive index and is used as an anti-reflection material to improve the light transmittance of the entire product; the coated glass of the present invention meets the tempering requirements, and various indicators before and after tempering meet the use requirements, and at the same time has the advantages of low resistance, high light transmittance and good processing resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a structural schematic diagram of the present invention. DETAILED DESCRIPTION
[0014] like Figure 1 As shown, a low-resistance, low-radiation, steelable triple-silver coated glass provided by the present invention comprises a glass substrate and 18 film layers deposited on the glass surface, and the structure of the three silver film layers is in the following order: glass substrate / base layer / first transition layer / first seed layer / first functional layer / first barrier layer / second transition layer / second dielectric layer / second seed layer / second functional layer / second barrier layer / third transition layer / third dielectric layer / third seed layer / third functional layer / third barrier layer / fourth transition layer / fourth dielectric layer / protective layer.
[0015] Figure 1 The structural layers are: Glass substrate layer 2, bottom silicon oxynitride layer 3, first transition layer niobium oxide layer 4. First seed layer zinc oxide layer 5. First functional layer silver yttrium layer 6. First barrier layer ITO layer 7. Second transition layer AZO layer 8. Second dielectric layer TZO layer 9. Second seed layer zinc oxide layer 10. Second functional layer silver yttrium layer 11. Second barrier layer ITO layer 12. Third transition layer AZO layer 13. The third dielectric layer TZO layer 14. The third seed layer zinc oxide layer 15. The third functional layer silver yttrium layer 16, a third barrier layer titanium layer 17, a fourth transition layer AZO layer 18, a fourth dielectric layer TZO layer 19, and a protective layer zirconium oxide layer.
[0016] As mentioned above, the low-resistance steel triple-silver low-radiation coated glass is mainly obtained by magnetron sputtering. The sputtering plane target uses a DC power supply, and the sputtering rotating target uses an AC power supply. The background vacuum in the coating chamber is as low as 1.0×10 -6 mbar, the target material purity is higher than 99.9%, and the process gas purity is higher than 99.999%.
[0017] The bottom layer is a silicon nitride oxide layer with a thickness of 15-20nm, which is obtained by the reaction after sputtering of a silicon-aluminum rotating target. The process gases used are argon, oxygen and nitrogen, and the deposition pressure is 0.0035mbar (Ar: O2: N2 = 3.2: 1: 2.3). The main function of this film layer is to connect the entire film layer with the glass substrate, so that there is a strong bonding force between the two (the film layer and the substrate are both silicon-based materials). The film layer is not easy to fall off during processing and use. At the same time, because the film layer is relatively dense, it can prevent the ions in the coated glass from diffusing to the functional layer during the tempering process, avoiding affecting the energy-saving effect of the glass; The first transition layer is a niobium oxide layer with a thickness of 5-10nm, which is obtained by sputtering a niobium oxide rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.005mbar (Ar:O2=50:1). Due to its high refractive index, this film layer can improve the transmittance of the entire product and play a certain role in enhancing transmittance. During the preparation process, trace amounts of oxygen in the atmosphere can adjust the electrical and optical properties of the single-layer film. The first seed layer is a zinc oxide layer with a thickness of 10-15nm, which is obtained by the reaction after sputtering of a zinc-aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.006mbar (Ar:O2=1:1.6); this film layer exists as a seed layer for the growth of the functional layer, which can make the surface of the prepared functional layer flatter.
[0018] The first functional layer is a silver-yttrium layer with a thickness of 12-18nm, which is obtained by sputtering a silver-yttrium alloy flat target. The process gas used is pure argon gas, and the deposition pressure is 0.003mbar. Compared with the traditional functional layer of pure silver layer, this functional layer adds the rare earth element yttrium. The addition of yttrium plays a role in refining the grains, improving the film quality, and improving the electrical properties of the film. Compared with the silver film layer, the silver-yttrium film layer of the same thickness has the advantages of denser film layer and lower contact resistance. The first barrier layer is an ITO layer with a thickness of 5-10nm, which is directly sputtered by an indium tin oxide rotating target. The process gas used is pure argon gas, and the deposition pressure is 0.003mbar. The main function of this film layer is to protect the first functional layer, and at the same time prevent the free oxygen in the subsequent film layer from moving to the functional layer during the tempering process to oxidize it, thereby reducing the overall energy-saving effect of the product. At the same time, compared with most protective layer materials (such as nickel chromium), the ITO material has a lower extinction coefficient, is transparent, and has certain electrical properties. While protecting the functional layer, it reduces the impact on the light transmittance of the product and increases the overall energy-saving effect of the product. The second transition layer is an AZO layer with a thickness of 8-12nm, which is obtained by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.004mbar (Ar:O2=50:1). This film layer is directly sputtered by a ceramic target zinc oxide aluminum. A trace amount of oxygen adjusts the light transmittance of the film layer. It has the characteristics of high sputtering rate and stable process, and is very suitable for the preparation of complex multi-silver products with more film layers. The second dielectric layer is a TZO layer with a thickness of 40-50nm. It is obtained by sputtering a zinc tin oxide target. The process gases used are argon and oxygen, and the deposition pressure is 0.004mbar (Ar:O2=50:1). This film layer is obtained by direct sputtering of zinc tin oxide from a ceramic target. A trace amount of oxygen adjusts the optical properties of the film layer. The sputtering speed is several times that of traditional materials (such as silicon nitride, zinc oxide, etc.). The process is stable and reliable, and is very suitable for use as a thicker dielectric layer (which can improve the production efficiency of the product).
[0019] The second seed layer is a zinc oxide layer with a thickness of 10-15nm, which is obtained by reaction after sputtering of a zinc-aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.006mbar (Ar:O2=1:1.6).
[0020] The second functional layer is a silver-yttrium layer with a thickness of 6-10nm, which is obtained by sputtering a silver-yttrium alloy flat target. The process gas used is pure argon gas, and the deposition pressure is 0.003mbar. Compared with the traditional functional layer of pure silver layer, this functional layer adds the rare earth element yttrium. The addition of yttrium plays a role in refining the grains, improving the film quality, and improving the electrical properties of the film. Compared with the silver film layer, the silver-yttrium film layer of the same thickness has the characteristics of denser film layer and lower contact resistance. The second barrier layer is an ITO layer with a thickness of 5-10nm, which is obtained by direct sputtering of an indium tin oxide rotating target. The process gas used is pure argon and the deposition pressure is 0.003mbar. The main function of this film layer is to protect the second functional layer and prevent the free oxygen in the subsequent film layer during the tempering process from moving to the functional layer to oxidize it, thereby reducing the overall energy-saving effect of the product.
[0021] The third transition layer is the AZO layer with a thickness of 8-12nm, which is obtained by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.004mbar (Ar:O2=50:1). This film layer is obtained by direct sputtering of zinc oxide aluminum on a ceramic target, and a trace amount of oxygen adjusts the light transmittance of the film layer.
[0022] The third dielectric layer is a TZO layer with a thickness of 50-60nm, which is obtained by sputtering a zinc tin oxide target. The process gases used are argon and oxygen, and the deposition pressure is 0.004mbar (Ar:O2=50:1). This film layer is obtained by directly sputtering zinc tin oxide from a ceramic target, and a trace amount of oxygen adjusts the optical properties of the film layer.
[0023] The third seed layer is a zinc oxide layer with a thickness of 10-15 nm, which is obtained by reaction after sputtering of a zinc-aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.006 mbar (Ar:O2=1:1.6).
[0024] The third functional layer is a silver-yttrium layer with a thickness of 10-15nm. It is obtained by sputtering a silver-yttrium alloy flat target. The process gas used is pure argon and the deposition pressure is 0.003mbar. Compared with the traditional functional layer of pure silver layer, this functional layer contains the rare earth element yttrium. The addition of yttrium can refine the grains, improve the film quality, and improve the electrical properties of the film. Compared with the silver film, the silver-yttrium film of the same thickness has the characteristics of denser film and lower contact resistance.
[0025] The third barrier layer is a titanium layer with a thickness of 0.8-1.2nm, which is obtained by sputtering a pure titanium flat target. The process gas used is pure argon gas, and the deposition pressure is 0.003mbar. The main function of this film layer is to protect the third functional layer, and at the same time prevent the free oxygen and nitrogen in the subsequent film layer from moving to the functional layer and destroying it during the tempering process, thereby reducing the overall energy saving effect of the product. When the outermost barrier layer is a metal material, it can improve the processing resistance of the product during deep processing. At the same time, compared with traditional nickel-chromium materials, titanium has a lower extinction coefficient, which can minimize the impact on light transmittance.
[0026] The fourth transition layer is the AZO layer with a thickness of 8-12nm, which is obtained by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.004mbar (Ar:O2=50:1); this film layer is obtained by direct sputtering of zinc oxide aluminum from a ceramic target, and a trace amount of oxygen adjusts the light transmittance of the film layer.
[0027] As described above, the low-resistance steel triple-silver low-emissivity coated glass is characterized in that the fourth dielectric layer is a TZO layer with a thickness of 25-35nm, which is obtained by zinc oxide tin target sputtering, and the process gases used are argon and oxygen, and the deposition pressure is 0.004mbar (Ar:O2=50:1); the film layer is obtained by direct sputtering of zinc oxide tin by a ceramic target, and a trace amount of oxygen adjusts the optical properties of the film layer.
[0028] The protective layer is a zirconium oxide layer with a thickness of 3-5nm, which is obtained by sputtering a zirconium oxide rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.003mbar (Ar:O2=100:1). The film layer is obtained by direct sputtering of zirconium oxide on a ceramic target. A trace amount of oxygen adjusts the optical properties of the film layer, and it has a higher hardness and a lower surface friction coefficient, which can effectively prevent the coated products from being scratched during transportation and deep processing.
[0029] The present invention also provides a method for preparing low-resistance, low-radiation, steelable three-silver coated glass, wherein the film layer structure is sequentially as follows from the glass substrate upward: glass substrate / silicon oxynitride layer / niobium oxide layer / zinc oxide / silver yttrium layer / ITO layer / AZO layer / TZO layer / zinc oxide / silver yttrium layer / ITO layer / AZO layer / TZO layer / zinc oxide / silver yttrium layer / titanium layer / AZO layer / TZO layer / zirconium oxide layer. Each single-layer film on the surface of the glass is mainly deposited by magnetron sputtering, and the glass substrate passes through different target sputtering zones of the coating zone of the production line in sequence through a servo motor, thereby sequentially depositing each designed single film layer on the glass surface, and the sputtering power and deposition atmosphere of each target material are set as required. The production line used is designed with multiple gas isolation components between different target materials, and the isolation coefficient is as high as 30 or more, which ensures the high purity of the atmosphere of various sputtering target materials, thereby ensuring the singleness of the components of each single-layer film, and the target film layer finally combined is the same as the designed structure.
[0030] The following is an explanation of three preferred embodiments, and the detailed process parameters of each glass and the optical parameters of the samples are shown in the following Tables 1-6.
[0031] Table 1 Process parameters of Example 1 product
[0032] Table 2 Optical parameters of the product in Example 1 before and after tempering
[0033] Table 3 Process parameters of Example 2 product
[0034] Table 4 Optical parameters of the product in Example 2 before and after tempering
[0035] Table 5 Process parameters of Example 3 product
[0036] Table 6 Optical parameters of the product in Example 3 before and after tempering
[0037] It can be seen from the above three groups of embodiments that the products have high visible light transmittance (up to 70%) and extremely low surface resistance (about 0.8Ω) after tempering, which is relatively rare for triple-silver coated products (having both low surface resistance and high visible light transmittance). The product optical parameters are not only suitable for the construction field, but also for the automotive glass industry. It is also applicable to the north and south regions, and has a wide range of usage scenarios.
[0038] The film structure and material selection of each single film minimize the mutual influence between the different atmospheres of each layer of the film during the preparation process, thereby greatly improving the stability and repeatability of the process. Such a production process is a huge advantage for enterprises (especially for triple-silver coated glass products with a higher technical level), which can greatly reduce the debugging time in the process of restoring the product, thereby reducing the production cost of the product.
[0039] 2.5% yttrium metal is doped into the silver functional layer, which refines the overall grain size of the target material, making the deposited functional layer denser and smoother. Compared with the pure silver layer of the same thickness, it has a lower surface resistance, and the product has excellent electrical properties and energy-saving effects. At the same time, the 2.5% yttrium doping enhances the hardness and corrosion resistance of the functional layer. Compared with traditional triple-silver coated glass, the product of the structure of the present invention has a shelf life of about 1.5 times before deep processing and tempering, which can greatly reduce the defective rate of triple-silver products during storage and deep processing, thereby reducing the company's financial losses in this regard.
Claims
1. A low-resistance, low-radiation, steelable triple-silver coated glass, comprising a glass substrate, Features: The three silver coating layers are sequentially arranged on the glass substrate: a primer layer, a first transition layer, a first seed layer, a first functional layer, a first barrier layer, a second transition layer, a second dielectric layer, a second seed layer, a second functional layer, a second barrier layer, a third transition layer, a third dielectric layer, a third seed layer, a third functional layer, a third barrier layer, a fourth transition layer, a fourth dielectric layer and a protective layer.
2. The low-resistance, low-radiation, steelable triple-silver coated glass according to claim 1, Features: The bottom layer is a silicon oxynitride layer with a thickness of 15-20 nm.
3. The low-resistance, low-radiation, steelable triple-silver coated glass according to claim 2, Features: The first transition layer is a niobium oxide layer with a thickness of 8-10nm, the first seed layer is a zinc oxide layer with a thickness of 10-13nm, the first functional layer is a silver yttrium layer with a yttrium content of 2.5% and a thickness of 12-18nm, and the first barrier layer is an ITO layer with a thickness of 5-10nm; The second transition layer is an AZO layer with a thickness of 8-12nm, the second dielectric layer is a TZO layer with a thickness of 40-50nm, the second seed layer is a zinc oxide layer with a thickness of 10-15nm, the second functional layer is a silver yttrium layer with a yttrium content of 2.5% and a thickness of 6-10nm, and the second barrier layer is an ITO layer with a thickness of 5-10nm; The third transition layer is an AZO layer with a thickness of 8-12nm, the third dielectric layer is a TZO layer with a thickness of 50-60nm, the third seed layer is a zinc oxide layer with a thickness of 10-15, the third functional layer is a silver yttrium layer with a yttrium content of 2.5% and a thickness of 10-15nm, and the third barrier layer is a titanium layer with a thickness of 0.8-1.2nm; The fourth transition layer is an AZO layer with a thickness of 8-12 nm, the fourth dielectric layer is a TZO layer with a thickness of 25-35 nm, and the protective layer is a zirconium oxide layer with a thickness of 3-5 nm.
4. A method for preparing a low-resistance, low-radiation, steelable triple-silver coated glass as claimed in claim 3, Features The following steps are involved: (1) A base silicon oxynitride layer with a thickness of 15-20 nm was prepared on a glass substrate by reaction after sputtering of a silicon-aluminum rotating target. The process gases used were argon, oxygen and nitrogen. The deposition pressure was 0.0035 mbar, Ar:O 2 :N 2 =3.2:1:2.3; (2) The first transition layer of niobium oxide is prepared on the base layer with a thickness of 5-10 nm. It is obtained by sputtering a niobium oxide rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.005 mbar, Ar:O 2 =50:1; (3) The first seed layer of zinc oxide is prepared on the first transition layer. The thickness is 10-15 nm. It is obtained by reaction after sputtering of zinc-aluminum rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.006 mbar, Ar:O 2 =1:1.6; (4) Preparing a first functional layer of silver-yttrium layer on the first seed layer, wherein the yttrium content is 2.5% and the thickness is 12-18 nm, obtained by sputtering a silver-yttrium alloy flat target, the process gas used is pure argon, and the deposition pressure is 0.003 mbar; (5) Preparing a first barrier layer ITO layer on the first functional layer with a thickness of 5-10 nm, obtained by direct sputtering of an indium tin oxide rotating target, using pure argon as the process gas and a deposition pressure of 0.003 mbar; (6) A second transition layer AZO layer with a thickness of 8-12 nm is prepared on the first barrier layer by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.004 mbar, Ar:O 2 =50:1; (7) A second dielectric layer TZO layer with a thickness of 40-50 nm is prepared on the second transition layer by sputtering of zinc oxide tin rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.004 mbar, Ar:O 2 =50:1; (8) A second seed layer of zinc oxide is prepared on the second dielectric layer. The thickness is 10-15 nm. It is obtained by reaction after sputtering of a zinc-aluminum rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.006 mbar, Ar:O 2 =1:1.6; (9) Preparing a second functional layer of silver-yttrium layer on the second seed layer, wherein the yttrium content is 2.5%, the thickness is 6-10 nm, and it is obtained by sputtering a silver-yttrium alloy flat target. The process gas used is pure argon gas, and the deposition pressure is 0.003 mbar; (10) Preparing a second barrier layer ITO layer on the second functional layer with a thickness of 5-10 nm, obtained by direct sputtering of an indium tin oxide rotating target, using pure argon as the process gas and a deposition pressure of 0.003 mbar; (11) A third transition layer AZO layer with a thickness of 8-12 nm is prepared on the second barrier layer by sputtering a zinc oxide aluminum rotating target. The process gases used are argon and oxygen, and the deposition pressure is 0.004 mbar. Ar:O 2 =50:1; (12) A third dielectric layer TZO layer with a thickness of 50-60 nm is prepared on the third transition layer by sputtering of zinc oxide tin rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.004 mbar, Ar:O 2 =50:1; (13) A third seed layer of zinc oxide is prepared on the third dielectric layer. The thickness is 10-15 nm. The layer is obtained by reaction after sputtering a zinc-aluminum rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.006 mbar, Ar:O 2 =1:1.6; (14) Preparing a third functional layer of silver-yttrium layer on the third seed layer, wherein the yttrium content is 2.5% and the thickness is 10-15 nm, obtained by sputtering a silver-yttrium alloy flat target, the process gas used is pure argon, and the deposition pressure is 0.003 mbar; (15) Preparing a third barrier titanium layer on the third functional layer with a thickness of 0.8-1.2 nm, obtained by sputtering a pure titanium flat target, using pure argon as the process gas and a deposition pressure of 0.003 mbar; (16) A fourth transition layer AZO layer with a thickness of 8-12 nm was prepared on the third barrier layer by sputtering a zinc oxide aluminum rotating target. The process gases used were argon and oxygen, and the deposition pressure was 0.004 mbar. Ar:O 2 =50:1; (17) A fourth dielectric layer TZO layer with a thickness of 25-35 nm is prepared on the fourth transition layer by sputtering of zinc oxide tin rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.004 mbar, Ar:O 2 =50:1; (18) A protective zirconium oxide layer with a thickness of 3-5 nm is prepared on the fourth dielectric layer by sputtering a zirconium oxide rotating target. The process gases used are argon and oxygen. The deposition pressure is 0.003 mbar, Ar:O 2 =100:1.